An immuno-potentiating vehicle made of mesoporous silica-zinc oxide micro-rosettes with enhanced doxorubicin loading for combined chemoimmunotherapy. Issue 7 (3rd January 2019) - Qian, Guowen; Wang, Xiupeng; Li, Xia; Ito, Atsuo; Sogo, Yu; Ye, Jiandong
Abstract : MS-Zn-DOX in combination with PIC not only significantly inhibit tumor growth, but also effectively rejects tumor metastasis in vivo, obviously improving CD4 + and CD8 + T cell populations and IFN-γ secretion in splenocytes of mice. Abstract : Herein, mesoporous silica-zinc oxide (MS-Zn) micro-rosettes with controllable petal thickness were synthesized by a facile one-pot hydrothermal method. MS-Zn loaded with doxorubicin and polyinosinic–polycytidylic acid sodium salt not only significantly inhibits tumor growth but also effectively rejects tumor metastasis in vivo .